Causal link of total locomotor activity, melatonin and rectal temperature daily rhythm in small ruminants - Claudia Giannetto; Carcangiu, Vincenzo; Luridiana, Sebastiano; Fazio, Francesco; Mura, Maria Consuelo; Parmeggiani, Albamaria; Piccione, Giuseppe (Journal of Applied Biomedicine, 2016)
To improve the knowledge in chronophysiology we investigated the causal link between the most important physiological variable studied until now; ten Sarda ewes and ten Sarda goats, pluriparus not pregnant and no lactating, were used. Animals were housed under natural environmental conditions in a common stall, alfalfa hay and water were available ad libitum. Each animal was equipped with an Actiwatch-Mini® for recording total activity. Blood samples were collected every 4 h over a 48 h period for the assessment of melatonin concentration. Rectal temperature was recorded with a digital thermometer immediately before the blood sampling at each data point. Single cosinor method showed a daily rhythm of studied variables. Higher MESOR and amplitude values of melatonin and rectal temperature were observed in sheep than in goats. The diurnal acrophase of locomotor activity was statistically different from the nocturnal acrophase of melatonin and rectal temperature, with no differences between the two species. Robustness was statistically lower in total locomotor activity in comparison with the others two variables, with a differences due to species in melatonin daily rhythm. In conclusion, in small ruminants, melatonin and rectal temperature daily rhythms are strictly correlated, and are not associated with the locomotor activity rhythm.
Keywords: cirkadiánní rytmus; pohybová aktivita; Goats; Melatonin; ovce; Animals; Motor Activity; Multivariate Analysis; Circadian Rhythm; Body Temperature; melatonin; zvířata; Sheep; multivariační analýza; kozy; tělesná teplota